2019
DOI: 10.1177/0271678x19831022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite concentration changes associated with positive and negative BOLD responses in the human visual cortex: A functional MRS study at 7 Tesla

Abstract: Negative blood oxygenation–level dependent (BOLD) signal observed during task execution in functional magnetic resonance imaging (fMRI) can be caused by different mechanisms, such as a blood-stealing effect or neuronal deactivation. Electrophysiological recordings showed that neuronal deactivation underlies the negative BOLD observed in the occipital lobe during visual stimulation. In this study, the metabolic demand of such a response was studied by measuring local metabolite concentration changes during a vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
52
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 94 publications
(117 reference statements)
6
52
4
Order By: Relevance
“…Our results are in line with recent findings showing that the average concentration of GABA during high contrast checkerboard stimulation was no different from a resting baseline (Kurcyus et al, 2018). Decreases in GABA with functional stimulation have been shown in the motor cortex using a sustained task (10 min hand clenching) and a GABA-edited sequence (Chen et al, 2017), whereas another study has found decreases in GABA in the visual cortex corresponding to a region of sustained negative BOLD response (Boillat et al, 2019). As GABAergic neurons represent 15%-30% of the total population (DeFelipe and Fariñas, 1992), sustained stimulation (Chen et al, 2017) and edited MRS sequences optimized for GABA, such as MEGA-PRESS (Mescher et al, 1998;Mullins et al, 2014), may be necessary to improve sensitivity to modulation of inhibitory activity in the early visual cortex.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with recent findings showing that the average concentration of GABA during high contrast checkerboard stimulation was no different from a resting baseline (Kurcyus et al, 2018). Decreases in GABA with functional stimulation have been shown in the motor cortex using a sustained task (10 min hand clenching) and a GABA-edited sequence (Chen et al, 2017), whereas another study has found decreases in GABA in the visual cortex corresponding to a region of sustained negative BOLD response (Boillat et al, 2019). As GABAergic neurons represent 15%-30% of the total population (DeFelipe and Fariñas, 1992), sustained stimulation (Chen et al, 2017) and edited MRS sequences optimized for GABA, such as MEGA-PRESS (Mescher et al, 1998;Mullins et al, 2014), may be necessary to improve sensitivity to modulation of inhibitory activity in the early visual cortex.…”
Section: Discussionsupporting
confidence: 93%
“…For lower image contrasts, glutamate is below baseline, although not significantly so. These changes are unlikely due to negative BOLD signal (Boillat et al, 2019), as BOLD responses were significantly higher than baseline at all contrast levels (Fig. 4A).…”
Section: Discussionmentioning
confidence: 90%
“…We showed that an extensive number of brain metabolites can be measured non-invasively in the human brain at ultra-high magnetic field of 7 T (Tkáč et al, 2001). We subsequently demonstrated that changes in neural activity are associated with relatively small changes in several metabolite concentrations which could be reliably detected at 7 T (Mangia et al, 2007a, b; Bednařík et al, 2015, 2018), as confirmed by other labs (Lin et al, 2012; Schaller et al, 2013, 2014; Boillat et al, 2019). The capability to measure these functional changes provides unique insights into how brain metabolism is associated with neural activity (Mangia et al, 2009).…”
Section: Introductionsupporting
confidence: 75%
“…There is a large body of evidence from fMRI studies that DMN is implicated in various brain diseases. 1 We suggest that applied task distinguishes the definition of task-positive and task-negative brain areas, such as VC could be activated by whole-screen flashing checkerboard 35 as well as deactivated by small flashing checkerboard 3,6 and visual-spatial attention. 7,8…”
Section: Introductionmentioning
confidence: 99%